Comparison of vo2 max among aerobic, bharathanatyam and kandyan dancers. - Sabaananth, S.; Gopinath, V. (Arul Anandar College, Madurai, 2013)
The purpose of this study was to compare VO2 max among bharathanatyam, kandyan and aerobic dancers. To achieve the purpose ninety (N=90) women dancers were selected from India and Sri lanka, and their age were 17 ± 1.3 years. They were classified in to Aerobic dance [(AD)( n=30, from India, practice aerobic dance 60±15 min / day/ 5 days / week over the period of minimum 3 years)], Bharathanatym Dancers [(BD) (n=30, from Sri lanka, practice bharathanatyam 60±15min / day for 5 days / week over the period of minimum 3 years)] and Kandyan Dancers [(KD)( n=30, from Sri lanka, practice kandyan dance 60±15 min / day/ 5 days / week over the period of minimum 3 years)]. VO2 max was assessed for all the selected subjects by Queen’s step test, the collected data were statistically treated by using one way ANOVA, 0.05 level of confidence was fixed to test the significance. When the obtained ‘F’ ratio was significant. Scheffe’s post hoc test was used to find out the paired mean difference. Within the limitations set for this study, it was concluded, that all the three dance groups were significantly differ on VO2 max. However aerobic dancers have better VO2 max than the bharathanatyam and kandyan dancers.
Keywords: Aerobic; Bharathanatyam; Kandyan; Dance VO2 max